The burden of proof rule under EU non-discrimination law and algorithmic discrimination - Blaker Strand, Vibeke (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2025)
Emerging technologies, including artificial intelligence, present significant challenges to discrimination law, particularly regarding effective enforcement. This article highlights the evidentiary difficulties in proving algorithmic discrimination and examines the rule on the burden of proof under EU non-discrimination law in this context. It discusses challenges and possibilities relating to the role of the burden of proof rule in enhancing the principle of equality and non-discrimination, particularly in relation to algorithmic discrimination. A key obstacle is the lack of transparency, a problem not unique to algorithmic discrimination but also a well-known challenge in the field of pay discrimination. The article argues that valuable insights can be drawn from how the burden of proof rule has been developed and concretised under EU law on the right to equal pay between women and men, with particular attention to the 2023 Pay Transparency Directive.
Keywords: algoritemska diskriminacija; dokazi; enako plačilo; enakost; pravo EU; učinkovito izvrševanje; umetna inteligenca